Students’ Perception About Mobile Learning in Morocco: Survey Analysis - Zidoun, Youness; El arroum, Fatima-Zohra; Talea, Mohamed; Dehbi, Rachid (International Journal of Interactive Mobile Technologies (iJIM), 2016)
Given the emergence of new mobile devices (tablet, PDA and smart phone), and the growth that knows that part of the ICT, integrating these new technologies into the learning system was imposed, and a new way of learning was born. Mobile learning or "m-learning" is providing great opportunities for learners, especially to learn anytime and anywhere without limitations. There is a new generation of students who grew up using technology and who are easily related to new mobile devices. We discuss the identity of mobile learning and aim to measure the interest of students on it through a survey. This survey seeks to promote mobile learning within the student’s community for a possible adoption in Moroccan higher education. Qualitative and quantitative approaches are endorsed. The results are analyzed, conclusions and perspectives presented at the end of this paper.